Bandwidth Management in Wireless Home Networks for IPTV Solutions. (5th March 2013) - Jursonovics, Tamás; Imre, Sándor
Abstract : The optimal allocation of the retransmission bandwidth is essential for IPTV service providers to ensure maximal service quality. This paper highlights the relevance of the wireless transport in today's IPTV solution and discusses how this new media affects the existing broadcast technologies. A new Markovian channel model is developed to address the optimization issues of the retransmission throughput, and a new method is presented which is evaluated by empirical measurements followed by mathematical analysis.